计算:7a²b-(-4a²b+5ab²)-2(2a²b-3ab²)
4个回答
7a²b-(-4a²b+5ab²)-2(2a²b-3ab²)
=7a²b+4a²b-5ab²-4a²b+6ab²
=(7a²b+4a²b-4a²b)-(5ab²-6ab²)
=7a²b-ab²
相关问题
计算(3a^2b-7ab^2-a^2b^2)`5ab
若ab=-7,a-b=7,求(2a+3b-2ab)-(a+4b+ab)-(3ab-2a+2b)的值.
(2a-7b)(3a+4b-1) 和 5ab*(-4b)+(-7ab)*(-ab)-ab*(-5a)拜托各位大神
7a²b+(-4a²+5ab²)-(2a²-3ab²)
计算a²/(a²-2ab)×√(a²b-4ab²+4b^3)/a+b√(a/b)
|a+b-7|+(ab+3)=0 求5a-3ab-4b-7a-11ab+2b的值
计算[(a^2-4b^2)/(a^2+4ab+4b^2)]÷[(a^2+ab-6b^2)/(a^2+5ab+6b^2)]
化简:7a²b + (4a²b - 5a²b)- 2(2a²b-3ab²
下列计算正确的是( ) A.7a-a=6 B.2a+b=2ab C.3a+a=4a 2 D.-ab+2ab=ab